De sitter-invariant approach to cosmology - Salazar Malpartida, Johan Renzo (2022)
A crucial problem of spacetime physics is the lack of a special relativity that could describe the Planck scale kinematics. The problem stems from the existence of an invariant length at the Planck scale, dubbed Planck length. Since the Poincaré- invariant Einstein’s special relativity does not admit an invariant length, it cannot describe the Planck scale kinematics. A possible solution to this puzzle is to replace the Poincaré-invariant Einstein’s special relativity with a de Sitter-invariant special relativity. Considering that the latter admits a finite invariant length while preserving the Lorentz symmetry, it meets the quantum requirements of the Planck scale physics and provides a consistent description of the Planck scale kinematics. Under such replacement, general relativity changes to the de Sitter-invariant general relativity, which differs substantially from ordinary general relativity. In this thesis, the associated de Sitter-invariant Friedmann equations are obtained, and a discussion of the main consequences for cosmology is presented